2021
DOI: 10.1111/jfpe.13680
|View full text |Cite
|
Sign up to set email alerts
|

Manifestation of neuro‐fuzzy simulation environment for prognostication of water absorption kinetics of soybean grains in thermo‐ultrasonication‐assisted soaking process

Abstract: Neuro‐fuzzy simulation of food engineering phenomena can be a supportive manner for integrated realization of compound trends of involved parameters. This article is aimed to manifest neuro‐fuzzy simulation environment for prognostication of water absorption kinetics of soybean grains in thermo‐ultrasonication‐assisted soaking process. The simulation environment was developed based on various types and numbers of input membership functions, defuzzification methods, types of output membership functions, and num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 106 publications
(129 reference statements)
0
8
0
Order By: Relevance
“…This mechanism creates microchannel, thus improving mass transfer (Miano et al, 2017). Similar studies dealt with ultrasound technology in water absorption process of agricultural products (Borsato, Jorge, Mathias, & Jorge, 2019; Guimaraes, Polachini, Augusto, & Telis‐Romero, 2020; Li et al, 2019; Miano et al, 2018; Miano, Rojas, & Augusto, 2019; Shafaei et al, 2021a; Shafaei et al, 2021b; Shafaei, Nourmohamadi‐Moghadami, & Kamgar, 2019; Shafaei, Nourmohamadi‐Moghadami, Rahmanian‐Koushkaki, & Kamgar, 2019; Yildirim et al, 2011; Yildirim, Bayram, & Mehmet, 2012; Yildirim, Öner, & Bayram, 2010) confirms this research. Increase in mass diffusion of cowpea during soaking may be decrease in cooking time of cowpea.…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…This mechanism creates microchannel, thus improving mass transfer (Miano et al, 2017). Similar studies dealt with ultrasound technology in water absorption process of agricultural products (Borsato, Jorge, Mathias, & Jorge, 2019; Guimaraes, Polachini, Augusto, & Telis‐Romero, 2020; Li et al, 2019; Miano et al, 2018; Miano, Rojas, & Augusto, 2019; Shafaei et al, 2021a; Shafaei et al, 2021b; Shafaei, Nourmohamadi‐Moghadami, & Kamgar, 2019; Shafaei, Nourmohamadi‐Moghadami, Rahmanian‐Koushkaki, & Kamgar, 2019; Yildirim et al, 2011; Yildirim, Bayram, & Mehmet, 2012; Yildirim, Öner, & Bayram, 2010) confirms this research. Increase in mass diffusion of cowpea during soaking may be decrease in cooking time of cowpea.…”
Section: Resultsmentioning
confidence: 91%
“…The equilibrium moisture content ( M e ) of cowpea was also increased as the temperature increased for all treatments (Table 1). This increase of equilibrium moisture content is a result of expansion of spaces and pores inside the grains which leads to more absorption of water (Miano & Augusto, 2018; Shafaei et al, 2021a). D eff changes at all temperatures were significant ( p ≤ .05) and temperature affected on D eff values of cowpea during conventional and ultrasound treated at different amplitudes (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, another scheme (ultrasonication) has been employed to proliferate water absorption of agricultural food products. Literature screening process confirmed that ultrasonication scheme was successfully utilized for soaking process of rice (Li et al, 2019;Wambura et al, 2008), chickpea (Ranjbari et al, 2013;Yildirim et al, 2010Yildirim et al, , 2011Yildirim et al, , 2012Yildirim et al, , 2013Yildirim & Oner, 2015), bean (Ghafoor et al, 2014;Lopez et al, 2017;Miano & Augusto, 2018a;Miano et al, 2016bMiano et al, , 2019aMiano et al, , 2018Miano et al, , 2019cUlloa et al, 2015), sorghum (Miano et al, 2016a;Patero & Augusto, 2015), melon (Miano et al, 2016a), sea cucumber (Zhang et al, 2016a(Zhang et al, , 2016b, carrot (Ricce et al, 2016), corn (Miano et al, 2017), wheat (Guimaraes et al, 2020;Shafaei et al, 2018aShafaei et al, , 2019c, potato (Miano et al, 2019b), barley (Borsato et al, 2019;Carvalho et al, 2018;Shafaei et al, 2019a), pumpkin (Rojas et al, 2020), paddy (Kalita et al, 2021), and soybean (Shafaei et al, 2021a). In these works, modeling hydration kinetics of the food products was commonly fulfilled with respect to soaking time using above-mentioned nonlinear models for certain soaking temperatures, constants, and coefficients of the models varied with variations in soaking temperature.…”
Section: Introductionmentioning
confidence: 97%